Romanian Deposit Guarantee Scheme and the Requirements of the Acquis Communautaire - Cristian Bichi (Romanian Journal of European Affairs)
This paper compares the Romanian and EU deposit insurance legislation in order to identify the changes, which are needed in order to obtain a full compatibility of the national regulations in the field of deposit protection with the corresponding European rules. The first part outlines the main features of the EU Directive 94/19/EEC on deposit guarantee schemes in order to find out to what extent Romania is bound to incorporate the relevant acquis communautaire into its national legislation. It results that the directive contains explicit harmonization provisions as regards the minimum level of protection (EUR 20,000), depositor co-insurance, types of depositors, instruments and currencies to be covered, nature of coverage, status of branches from EU and non-EU countries, the compensation period and information to depositors. The directive does not provide for the harmonization of the financial and administrative structure of the deposit guarantee schemes, Romania being free to choose from a wider range of options. The second part examines the legal environment of deposit protection in Romania. The third part identifies the measures to be taken by the Romanian authorities in order to fill in the remaining regulatory gaps in the area of deposit insurance. Finally, the fourth part contains the conclusions.